DARI CATATAN KE KEMANDIRIAN BELAJAR: PRAKTIK PEMBIASAAN MENCATAT SANTRI DALAM PEMBELAJARAN FIQIH DI PESANTREN - Mustakin; Efendy, Rustan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Fiqh learning in Islamic boarding schools requires not only mastery of Islamic legal concepts but also students’ learning readiness, active participation, and independence in understanding and internalizing the material. However, note-taking is often perceived as a mechanical activity carried out after the teacher explains the lesson, rather than as an independent learning strategy before classroom instruction begins. This study aims to describe students’ note-taking habituation practices in Fiqh learning, analyze their function as a learning strategy, and identify the supporting and inhibiting factors in the formation of this habit. This research employed a qualitative approach with a case study design at Al-Urwatul Wutsqaa Islamic Boarding School. The informants consisted of eight tenth-grade students, one Fiqh teacher, and the head of the boarding school, selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, then analyzed thematically through open coding, categorization, and theme development. The findings show that students’ note-taking practices occur in reactive, proactive, and mixed patterns. Notes function cognitively to support comprehension and memory, socially to facilitate discussion and question-and-answer activities, evaluatively as a learning resource for examinations, and affectively to foster discipline. Note-taking habituation is influenced by personal awareness, teacher guidance, peer influence, and the boarding school culture, but is hindered by laziness, fatigue, dormitory distractions, and difficulties in identifying key points. These findings are significant because they position note-taking as a pre-learning strategy that supports students’ learning independence. Practically, this study can serve as a basis for teachers and Islamic boarding schools to develop a more structured, reflective, and meaningful Fiqh learning culture.